What about perennial grains? - Andrén, Karin; Kuylenstierna, Ebba (2022)
This thesis aims to create an understanding of how structures affect grain producers’ work with sustainability, and to investigate if perennial grains can be part of the future grain production in Sweden. The agricultural sector is facing a dilemma, both to ensure that ecosystem services are kept intact but also to keep up the global food supply for the growing population. Today’s efficient industrial agriculture has contributed to increased emissions and the sector needs a sustainability transition. The food and agriculture industry has a strongly institutionalised structure, which means that fundamental changes take a particularly long time. Swedish grain producers are affected by structures from different levels within the sector which affect their possibility to act sustainable within their business. The current cultivation systems with annual grains requires a lot of tillage which contributes to a lot of emissions. Perennial grains are used in other countries but not yet integrated into the Swedish agricultural sector. The ongoing research development of perennial grains in Sweden is to adapt the crop to the Nordic climate and to develop a perennial grain that can be compared with the current yield and profitability of annual grains. The data collection in this thesis has been conducted through semi-structured interviews with six grain producers in Skaraborg, Västra Götaland. The theoretical framework in the thesis consists of structuration theory and sustainability transitions. The concept duality within structuration theory with structures and actions are applied on the different MLP-levels within sustainability transitions to analyse how the selected grain producers are affected by structures from the different levels and how their individual agency is affected. The results reveal that the institutionalised structures affect the grain producers’ attitude towards sustainability within their business through both change inertia and the fear of lowered profitability. Joint structural changes within politics, research and development, consumers, and the grain producers themselves; are needed before the respondent perceives an opportunity to act more sustainably within their day-to-day operations. Most of the respondents consider perennial grains to be more interesting if they had better characteristics such as higher profitability, higher yield, and a higher market demand. The attitude towards perennial grains is positive but the perceived risk of low profitability inhibits implementation. By analysing the grain producers’ own context with selected theoretical framework: This study shows that a supporting system is needed that enables increased profitability for sustainable initiatives and sustainability through all levels. Researchers and retailers are important actors in creating resources and structures that make it easy for grain producers to act sustainably. The grain producers themselves need to take risks when they are in situations where they have a choice to act sustainably.